Penguatan Kompetensi Publikasi Mahasiswa Tingkat Akhir Melalui Coaching Clinic Penulisan dan Submit Artikel Ilmiah di Program Studi Pendidikan Teknologi Informasi FT UNG - H., Haeriani; Ashari, Sri Ayu; Nadifa, Ulfatun; Larosa, Esra; Asri, Aristi Ayuningsi Ode; Pratama, Musfir Rizal (Jurnal Sibermas (Sinergi Pemberdayaan Masyarakat), 2024)
The preparation of scientific articles is an important aspect in the academic world, especially for final year students. Lack of student understanding in writing scientific articles is a problem so it is expected that through strengthening student competency through the Coaching Clinic, difficulties in the process of submitting scientific articles, errors in writing format and plagiarism can be minimized. The Coaching Clinic was held by the Informatics Engineering Department for final year students of the information technology education study program (semesters 7 and 9). The implementation method is carried out by data collection, analysis, implementation and evaluation. Based on the results of the pre-test and post-test calculations, it showed a significant increase in student understanding in writing scientific articles, where the average post-test score (85.6%) was consistently higher than the pre-test score (46.8%). This proves that the socialization activities carried out effectively increased student understanding, so that the objectives of the activity could be achieved properly.